Short Term Radiological Outcome of Combined Femoral and Ilium Osteotomy in Pelvic Reconstruction of the Child - Lorenz Pisecky; Gerhard Großbötzl; Stella Stevoska; Matthias Christoph Michael Klotz; Christina Haas; Tobias Gotterbarm; Matthias Luger; Manuel Gahleitner (MDPI AG, 2022)
Background and Objectives: Reconstruction of the pelvic joint is a common way to address developmental dysplasia of the hip (DDH), as well as neurogenic dislocation of the hip (NDH) and Legg-Calvé-Perthes disease (LCPD) in children. The purpose of this study was to analyze the short-term radiologic outcome after hip reconstructive surgery either treated with sole osteotomy of the femur or in combination with iliac osteotomy in patients with DDH, NDH and LCPD. Materials and Methods: X-rays of 73 children, aged 2-18 years, with DDH, NDH and LCPD after hip reconstructive surgery were measured retrospectively and compared to the preoperative x-rays concerning various parameters to define hip geometry. The surgical procedures were femoral osteotomy (74), Salter innominate osteotomy (27), Pemberton osteotomy (27), open reduction (37), Chiari osteotomy (4). The pre-/postoperative acetabular index (AI), center-edge angle (CE) and Reimers migration index (RMI) were evaluated before and 3 months after surgery. Results: Hip geometry parameters improved significantly (RMI: preop/postop: 62.23% ± 31.63%/6.30% ± 11.51%, p < 0.001; CE: 11.53° ± 20.16°/30.58 ± 8.81°, p < 0.001; AI: 28.67° ± 9.2°/19.17 ± 7.65°, p < 0.001). Sub-group analysis showed a superior RMI in DDH compared with NDH 3 months after surgery (DDH/NDH: 2.77% ± 6.9%/12.94% ± 13.5%; p = 0.011). Osteotomy of the iliac bone (Salter innominate, Pemberton, Chiari) resulted in a significant improvement of the postoperative RMI compared to cases without osteotomy of the ilium (7.02 ± 11.1% vs. 16.85 ± 4.71%; p = 0.035). Conclusions: Femoral and pelvic osteotomies are effective to improve the radiological pelvic parameters in infants and adolescents with DDH, NDH and LCPD. In addition, the study found that the combination of femoral and pelvic osteotomy led to a better RMI than femoral osteotomy alone. Using the combined ilium and femoral osteotomy, it was possible to show the highest effect on correction of the hip geometry with respect to residual RMI.